INTERNAL CONTROL, ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH ACCOUNTING INFORMATION SYSTEM AS INTERVENING - Amira Amira; Ditya Permatasari (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
The purpose of this study is to find out the influence of internal control and organizational culture on employee performance with accounting information systems as intervening variables. The population in this study was employees of accounting and finance department in PT PG Rajawali I Unit PG Krebet Baru with a total of 45 people. This type of quantitative research. Data analysis used is multiple regression analysis by looking at the results of the coefficient of determination to determine the influence of intervening variables and descriptive statistical analysis. There are 7 hypotheses that can be formulated in this study. The results of the study are: 1) internal control has a positive and significant effect on employee performance; 2) organizational culture negatively and significantly affects employee performance; 3) accounting information system has a positive and insignificant effect on employee performance; 4) internal control has a positive and significant effect on accounting information systems; 5) organizational culture positively and significantly affects accounting information systems; 6) indirectly internal control through accounting information systems has a positive and insignificant influence on employee performance and 7) indirectly the culture of the organization through accounting information systems has a positive and significant influence on employee performance.